2005
DOI: 10.1002/ajh.20281
|View full text |Cite
|
Sign up to set email alerts
|

Venous thromboembolism prophylaxis in medically ill patients and the development of strategies to improve prophylaxis rates

Abstract: Venous thromboembolism (VTE) is common but often unrecognized in medically ill patients. Over the past 5 years, three large-scale placebo-controlled trials enrolling a total of 5500 medically ill patients have highlighted the risk of VTE in this group. These trials have helped to define a specific at-risk patient profile, including those admitted to the hospital with severe congestive heart failure, respiratory illness, acute infection, and inflammatory bowel disease. We performed a retrospective review of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
77
1
9

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(93 citation statements)
references
References 19 publications
6
77
1
9
Order By: Relevance
“…Prospective analysis, however, would have required patient consent with the potential for bias as patients being aware of the intervention would have placed pressure on clinicians to prescribe thromboprophylaxis, which may have skewed the results. 15 …”
Section: Limitations Of This Studymentioning
confidence: 99%
“…Prospective analysis, however, would have required patient consent with the potential for bias as patients being aware of the intervention would have placed pressure on clinicians to prescribe thromboprophylaxis, which may have skewed the results. 15 …”
Section: Limitations Of This Studymentioning
confidence: 99%
“…26,27 In a prospective registry of 5,451 patients with confirmed DVT, fewer medical patients received prophylaxis compared with surgical patients (32% versus 48%), 37 suggesting that QI interventions are particularly important for medical patients. A prospective study of the impact of continuing medical educa< tion and quality assurance programs on the use of VTE prophylaxis showed that statistically significant increases in the use of prophylaxis occurred in both medical and surgical patients in response to the interventions.…”
Section: Qi Initiatives For Preventing Vte In Surgical or Medical Patmentioning
confidence: 99%
“…7 In the Tooher et al review, most of the QI studies were performed in surgical patients. 8 However, several more recently published initiatives have focused on medical patients [26][27][28][29][30] (Table 3). A highly successful multifaceted strategy for improving appropriate VTE prophylaxis in medical patients combined education, dissemination of a decision support tool, and regular audit-and-feedback for resident physicians.…”
Section: Qi Initiatives For Preventing Vte In Surgical or Medical Patmentioning
confidence: 99%
See 2 more Smart Citations